Diurnal pattern of salivary alpha-amylase and cortisol under citric acid stimulation in young adults - Haimei Xie; Xiaomei Zheng; Ye Huang; Weihao Li; Wenkai Wang; Qiao Li; Jiangtao Hou; Lulu Luo; Xiuying Kuang; Chuan-quan Lin (PeerJ, 2022)
Background Saliva composition has diurnal variations. Citric acid stimulation plays a major role in the change of salivary flow rate and salivary composition. However, diurnal variations and sex differences in salivary alpha-amylase (sAA), pH, salivary flow rate (SFR), and salivary cortisol before and after citric acid stimulation remain unclear. Methods We recruited 30 healthy volunteers, including 15 women (24.7 ± 1.0 years old) and 15 men (25.3 ± 1.3 years old). At four time points (T1, 7:00; T2, 10:00; T3, 16:00; and T4, 20:00), saliva was collected from healthy volunteers before and after citric acid stimulation; and sAA, pH, SFR and salivary cortisol were measured and compared between men and women. Results There were circadian fluctuations in sAA activity, SFR, pH, and cortisol level both before and after citric acid stimulation, and the diurnal fluctuations of these indexes were not affected by citric acid stimulation. There were significant differences in salivary cortisol between men and women before and after acid stimulation in T1. Neither SFR nor pH showed sex-related differences before or after acid stimulation. The variation trend of sAA activity was contrary to that of cortisol, with a significant negative correlation. Conclusions Our data suggest that sAA and cortisol showed diurnal fluctuation, and the variation characteristics of male and female under resting state and acid stimulation were basically the same. The variation trend of salivary alpha-amylase activity was opposite to that of cortisol, with significant negative correlation. Our findings may enable the selection of the correct sampling time for research and the selection of appropriate sampling strategies in studies investigating chronic psychosocial conditions.